Using spectral continuity to extract breathing rate from heart rate and its applications in sleep physiology - Orphanides, Gregoris A.; Karittevlis, Christodoulos; Alsadder, Lujain; Ioannides, Andreas A. (Frontiers in Physiology, 2024)
ECG-derived respiration (EDR) is a set of methods for extracting the breathing rate from the Electrocardiogram (ECG). Breathing rate and more specifically the breathing pattern is a vital sign that is less employed than Electroencephalogram (EEG) and heart rate in sleep and polysomnography studies, even though recent studies revealed a tight connection between breathing patterns during sleep and several related pathologies. This study utilised open-access data from the ISRUC sleep database to test a novel spectral-based EDR technique. In contrast to previous approaches, the novel method emphasizes spectral continuity and not only the power of the different spectral peaks. The method showcased improved performance in terms of accuracy when compared against the classic method ( Bailon et al., 2006). Thus, proposing spectral continuity EDR (scEDR) as a potential low-cost and non-invasive method for extracting the breathing rate using the heart rate during sleep with further studies required to validate its accuracy in awake subjects. This study further explores the breathing rate across sleep stages, providing evidence in support of a putative sleep stage "REM0" which was previously proposed based on analysis of the Heart Rate Variability (HRV) but not yet widely discussed. Most importantly, this study observes that the frequency distribution of the heart rate during REM0 is closer to REM than other NREM periods even though most of REM0 was previously classified as NREM sleep by the sleep experts. Finally, the autonomic balance across different sleep stages including REM0 was explored using HRV as a metric, revealing that sympathetic activity decreases as sleep progresses to NREM3 until it reaches a level similar to the awake state in REM through a transition from REM0.